Comparison of the Vitamin D Status of Children Younger and Older Than 2 Years in Tehran: Are Supplements Really Necessary? - Torkaman, Mohammad (Int J Endocrinol Metab, 2016)
BACKGROUND: Vitamin D is a vital lipid-soluble vitamin in the body, helping the growth and development of bones. Vitamin D deficiency in children has several adverse effects. The most important preventative factor is determining the deficiency at an early stage and prescribing vitamin D-containing supplements. OBJECTIVES: To investigate the vitamin D status of children younger and older than 2 years and determine the utility of prescribing vitamin D supplements. PATIENTS AND METHODS: Three hundred healthy children who attended the pediatric clinic for routine assessments were enrolled in this study. Their parents were asked to complete a questionnaire, which included questions about demographics, nutrition, and supplements. Blood levels of vitamin D, calcium, and phosphorus were then measured. RESULTS: The final study consisted of 286 children, 140 males and 146 females, with a mean age of 4.46 ± 2.82 yr. Of these, 218 (76.22%) children, with a mean age of 5.09 ± 2.82 yr, had vitamin D deficiency, and 76 children (23.78%), with a mean age of 2.58 ± 1.88 yr, had normal vitamin D levels (P = 0.001). The mean level of vitamin D was 29.71 ± 14.42 ng/mL in 88 (30.8%) patients up to 2 years and 17.11 ± 14.02 ng/mL in 198 (69.2%) patients older than 2 years (P = 0.0001). CONCLUSIONS: The vitamin D levels of children aged more than 2 years are lower than those of children aged less than 2 years. Thus, prescribing vitamin D-containing supplements in children older than 2 years may be beneficial.